Mechanism of Roadway Floor Heave Controlled by Floor Corner Pile in Deep Roadway under High Horizontal Stress. (11th February 2021) - Kang, Xinchao; Guo, Dongming; Lu, Zhiying
Abstract : In order to overcome the support difficulty of serious floor heave caused by rock burst, with the floor heave of ventilation roadway in Hegang Xing An Coal Mine as the engineering background, the treatment scheme of the concrete-filled steel tube corner pile and floor grouting is put forward. Based on the solution of the slip line field under plane strain condition, the mechanical model of the slip-type floor heave is established, and the formula for calculating the critical failure depth of the roadway floor and the minimum support depth of the corner pile is derived. Through numerical analysis and similar model tests, the deformation and stress distribution of surrounding rock under the support of the corner piles are studied, and the force law of the pile under high horizontal stress is analyzed. The results show that, compared with the floor corner anchor, the floor corner pile + floor grouting support scheme can significantly improve the mechanical properties of the floor rock mass, and the plastic slip line of the floor plate part can be cut by corner piles, which effectively controls the deformation of the floor plate under high horizontal stress; the length and inclination angle of the corner pile have a great influence on the support effect. In the on-site treatment scheme, 1.1 times the calculated length of pile should be selected. The results of a similar model and field test show that the corner pile is effective in controlling the deformation of roadway floor and two sides.